TEACHING ISLAMIC STUDIES IN THE DIGITAL ERA: NAVIGATING OPPORTUNITIES AND CHALLENGES OF AI INTEGRATION IN EMERGING EDUCATIONAL CONTEXTS - Habibullah Habibi; Habibullah Ahmadi; Fayaz Ghafoori (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The integration of Artificial Intelligence (AI) in education is rapidly transforming teaching and learning processes worldwide. However, its adoption within Islamic Studies education remains limited and understudied, especially concerning theological accuracy and cultural appropriateness. This study aims to explore Islamic Studies educators’ awareness, usage, and perceptions of AI tools in teaching, alongside institutional support and future outlooks. Using a synthetic survey of 100 male educators from public and private universities, madrasahs, and online academies, data were collected on demographics, AI awareness, usage patterns, perceived opportunities, challenges, and ethical concerns. Quantitative analyses assessed mean ratings on familiarity, AI tool usage, and institutional readiness, supplemented by thematic summaries of open-ended responses. Results indicate moderate awareness of AI (mean = 3.2) but very low actual usage (mean = 2.0), with 50% of respondents never using AI tools. Educators recognize AI’s potential to improve access to Islamic knowledge and facilitate distance learning but express strong concerns regarding theological inaccuracies (mean = 4.6) and the erosion of spiritual teacher-student relationships (mean = 4.5). Institutional support and training were critically low. Despite reservations, 60% support AI integration under scholarly supervision, favoring a hybrid model balancing technology with traditional teaching. In conclusion, the study highlights a cautious yet optimistic stance towards AI in Islamic education, emphasizing the need for culturally grounded AI systems, enhanced educator training, and supportive policies to harness AI’s benefits while preserving religious integrity.